2005
DOI: 10.1107/s1600536805006021
|View full text |Cite
|
Sign up to set email alerts
|

2,2'-Diaminodibenzyl: a rare case of crystallographically non-compliant molecular symmetry

Abstract: The title compound, C14H16N2, adopts a trans‐planar conformation. However, the mol­ecule, which possesses Ci point group symmetry, crystallizes in the non‐centrosymmetric space group P212121. In the crystal structure, the mol­ecular symmetry is only approximately retained. The crystal packing is predominantly stabilized by N—H·N hydrogen bonds. Weak C—H·π inter­actions also contribute to the stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A similar compound 4-methyl-5-(4-nitrobenzylidene)-2oxo-2,5-dihydro-1H-pyrrole-3-carbonitrile (Gainsford et al, 2013) has already been reported and has a similar structure to the title compound. Narasegowda et al (2005) reported a case of chiral crystallization in space group P2 1 2 1 2 1 , the same space group as the title compound. In contrast, our recent examples of chiral crystals composed of achiral molecules both crystallize in space group P2 1 (Yagi et al, 2018;Yamazaki et al, 2018).…”
Section: Data Reportsmentioning
confidence: 98%
“…A similar compound 4-methyl-5-(4-nitrobenzylidene)-2oxo-2,5-dihydro-1H-pyrrole-3-carbonitrile (Gainsford et al, 2013) has already been reported and has a similar structure to the title compound. Narasegowda et al (2005) reported a case of chiral crystallization in space group P2 1 2 1 2 1 , the same space group as the title compound. In contrast, our recent examples of chiral crystals composed of achiral molecules both crystallize in space group P2 1 (Yagi et al, 2018;Yamazaki et al, 2018).…”
Section: Data Reportsmentioning
confidence: 98%
“…The crystal structures of three analogous compounds have been published thus far (Alcock et al, 2006;Sathiyanarayanan et al, 2007Sathiyanarayanan et al, , 2008. For molecular and crystal symmetry, see Yao et al (2002); Pidcock et al (2003); Narasegowda et al (2005); Schmidt et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…The molecular symmetry (C 2 ) is retained in the crystal of (III) and the asymmetric unit is composed of one-half of the molecule (Z′ = 1/2) as observed in (I), (II) and (IV). The database analysis has revealed that among organic molecules, there is a persistent tendency for molecular symmetry to be retained in the crystal (Yao et al, 2002), although exceptions to this general trend have also been reported even in the case of inversion center that is mostly conserved (Narasegowda et al, 2005;Schmidt et al, 2006). Recent work (Pidcock et al, 2003) has led to the conclusion that the C 2 point group symmetry is conserved in about 60% of ther reported cases.…”
Section: S1 Commentmentioning
confidence: 99%
“…The crystal structures of three analogous compounds have been published thus far (Alcock et al, 2006;Sathiyanarayanan et al, 2007Sathiyanarayanan et al, , 2008. For molecular and crystal symmetry, see Yao et al (2002); Pidcock et al (2003); Narasegowda et al (2005); Schmidt et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…The molecular symmetry (C 2 ) is retained in the crystal of (II) and the asymmetric unit is composed of one-half of the molecule (Z′ = 1/2) as observed in (I), (III) and (IV). The database analysis has revealed that among organic molecules, there is a persistent tendency for molecular symmetry to be retained in the crystal (Yao et al, 2002), although exceptions to this trend have also been reported even in case of inversion center that is mostly conserved in the crystal (Narasegowda et al, 2005;Schmidt et al, 2006). Recent work (Pidcock et al, 2003) has led to the conclusion that the C 2 point group symmetry is conserved in about 60% of the reported cases.…”
Section: S1 Commentmentioning
confidence: 99%